Amelioration of experimental autoimmune uveoretinitis by inhibition of glyceraldehyde-derived advanced glycation end-product formation. Issue 6 (8th September 2014) - Dong, Zhenyu; Iwata, Daiju; Kitaichi, Nobuyoshi; Takeuchi, Masayoshi; Sato, Masashi; Endo, Noriko; Iwabuchi, Kazuya; Ando, Ryo; Fukuhara, Junichi; Kinoshita, Satoshi; Lennikov, Anton; Kitamura, Mizuki; et al.
Abstract : Formation of glyceraldehyde-derived advanced glycation endoproducts contributes to the pathogenesis of endogenous uvetitis in human and animals. Abstract: AGEs are permanently modified macromolecule derivatives that form through nonenzymatic glycation of amino groups of proteins. Glycer-AGEs are highly toxic and play an important role in the pathogenesis of chronic inflammatory diseases. However, the contribution of glycer-AGEs to the pathogenesis of uveitis is unclear. In this study, we measured serum levels of glycer-AGEs in 100 patients with endogenous uveitis (22 with HLA-B27-associated uveitis, 20 with VKH disease, 14 with Behçet's disease, and 44 with sarcoidosis) and 33 healthy volunteers. We then examined the effect of the AGE inhibitor in a mouse model of human endogenous uveitis (EAU) by continuous oral administration of pyridoxamine at 200 or 400 mg/kg/day. Regardless of the etiology, serum glycer-AGE levels were significantly higher in patients with uveitis than in healthy subjects. Treatment with 400 mg/kg pyridoxamine significantly reduced the clinical and histological severity of EAU and was accompanied by a significant decrease in serum and retinal glycer-AGE levels and suppression of translocation of NF-κB p65 into the nucleus of retinal cells. Serum glycer-AGE levels may therefore serve as a biomarker of human uveitis, as well as systemic inflammation, and may contribute to the progression of uveitis, including diabetic iritis, via the activation of NF-κB.